Development and validation of core technology competencies for systems librarian - Naveed, Muhammad Asif; Siddique, Nadeem; Mahmood, Khalid (Digital library perspectives, 2022)
Purpose This study aimed to develop and validate a list of core technology competencies for systems librarian in Pakistan. Design/methodology/approach Survey method was used to conduct this investigation. A structured questionnaire, consisting of 52 competency statements categorized into six core technology areas, was developed based on an extensive literature review, experts’ scrutiny and pilot testing. The administration of the survey questionnaire was done though online environments such as related listservs and Facebook pages. The received 62 responses were imported into statistical package for social sciences and analyzed by computing means, standard deviations, Pearson correlation and t-test. Findings The results indicated six core technology areas where competencies of systems librarians needed to be developed, namely, basic computing, programming and Web publishing, computer networks, cloud computing, database management systems and information systems. The respondents validated 50 statements with an average mean score more than three. Only two statements received mean scores less than three. The results also indicated higher consistency of these statements as the value of Cronbach’s alpha was 0.973. Research limitations/implications This research attempted to identify and validate core technology competencies needed for systems librarians in Pakistan. It neither attempted to determine the weightage each competency should have if it was to be included in curriculum nor it intended to identify a detailed content for each core technology competency. In Pakistan, System librarians develop their knowledge and skills with the specialized computer subject by studying on their own, attending training workshops and on job experience. It is therefore worth mentioning here that the knowledge of the needed competencies may be limited. Practical implications Library and information science schools need to consider these competencies in developing and designing information curriculum with regard to management of library systems. This set of competencies help academicians in designing need-based curricula and training programs for existing and prospect system librarians in Pakistan. Originality/value This study would be a worthwhile contribution to the literature on competencies of information professionals especially systems librarians as no such study appeared providing pragmatic, evidenced and field-based insights toward proposed research area.